O wartości logicznej enigmatycznych odpowiedzi - Lapis, Włodzimierz (Investigationes Linguisticae, 2004)
The data discussed in the article have been collected from web pages and include sentences containing phrases: I don’t confirm or I don’t deny and compounds of both (also sentences containing synonymous phrases). The meaning of these sentences is discussed not only in their literal sense, but also in the intentional one (following the way of author’s thinking) or in the interpretative one (how the meaning was understood by its recipient).